KOMPLEKSITAS PERUSAHAAN, UKURAN PERUSAHAAN, DAN RISIKO AUDIT TERHADAP FEE AUDIT - Ningsih, Nurul Hutami; Darmayanti, Darmayanti; Asterina, Fenty; Afrida, Anggrelia; Suprayogi, Yogi (Universitas Muhammadiyah Palembang, 2024)
This research was conducted to determine the relationship between company complexity, company size, and audit risk on audit fees in manufacturing companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange for the 2018-2022 period using secondary data, namely annual financial report data of industrial sector manufacturing companies. basics and chemistry. The type of research used is associative research. The population in this study was 75 companies and the samples taken were 17 companies. The data collection technique used is documentation. The data analysis method in this research is quantitative analysis using several techniques, namely classical assumption testing, multiple linear regression analysis, coefficient of determination and hypothesis testing assisted by data processing applications, namely Statistical Product And Service Solutions (SPSS). The results show that company complexity, company size, and audit risk influence audit fees.